Sistem skoring faktor risiko sebagai model prediktor kejadian cedera sfingter ani obstetrik - Arufiadi Anityo Mochtar; Surahman Hakim; Tyas Priyatini; Shirley Anggraini Tunggadewi; Erwinanto Erwinanto; M Thohar Arifin (Intisari Sains Medis, 2018)
ABSTRACTIntroduction: anal sphincter injury is one of the complications that often occur in vaginal delivery. The impact of anal sphincter injury after vaginal delivery can reduce quality of life by causing various complaints such fecal incontinence, voiding disorders, sexual dysfunction, perineal pain and rectovaginal fistula. Assessment of risk factors is important to watch out for patients who are more prone to injury to the anal sphincter. This study aims to obtain a scoring system of various antenatal risk factors that can be used to predict the incidence of obstetric anal sphincter injury.Methods: This study is a diagnostic test that uses predictive factors for various risk factors for anal sphincter injury in vaginal delivery. The research was carried out in maternity service at Dr. Cipto Mangunkusumo General Hospital and Fatmawati General Hospital in the period February - July 2016. Analysis of the data in this study uses SPSS version 21.0. The analysis test used in this study is the calculation of odds ratio, logistic regression test, ROC curve analysis test to assess sensitivity and specificity of the scoring system.Results: Nulliparous, estimated fetal weight ≥ 3,500 gr, perineum length ≤ 25 mm, estimated head circumference ≥33.5 were risk factors for obstetric anal sphincter injury (OR> 1; p <0.05). Through the scoring modeling system all risk factors can be converted into scores 1. The probability values of scores 1, 2, 3, 4 are 7%, 30%, 70% and 90% respectively. The sensitivity and specificity of the scoring system developed were 61.3% and 91.3% with a cut-off score of 2.Conclusion: By knowing the prediction score before delivery, action can be taken to prevent the possibility of sphincter injury in obstetrics.